Synthesis of Nanostructured Mg2Ni for Hydrogen Storage by Mechanical Alloying via High-Pressure Torsion - Edgar Ignacio López Gómez; Joaquín Gonzalez; Jorge M. Cubero-Sesin; Jacques Huot (Reactions)
Mg2Ni is a highly promising candidate for solid-state hydrogen storage due to its high storage capacity. However, its synthesis is challenging due to the high melting point of Ni (1455 °C) and the boiling point of Mg (1090 °C). In this study, elemental powder mixtures of Mg and 30 at% Ni were processed by high-pressure torsion (HPT) to synthesize the Mg2Ni intermetallic compound through mechanical methods. The formation of 11 wt% of Mg2Ni after 50 turns of HPT was confirmed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS), reaching a maximum of 59 wt% after 100 turns. Rietveld refinement confirmed a nanocrystalline size for the Mg2Ni phase synthesized via HPT. Hydrogenation tests showed that the Mg-Ni synthesized by HPT can absorb hydrogen at 350 °C even after several weeks of air exposure. Furthermore, a maximum absorption capacity of 3.8 wt% was reached after 20 h of hydrogen exposure for the sample with 100 turns. This capacity is close to the theoretical capacity of 3.9 wt% for this composition. The results confirm that combining HPT with subsequent heat treatment is an efficient strategy to increase the Mg2Ni fraction after HPT processing.